Evaluación del Efecto de dos Compost en combinación con un Fortificador (wayra) en el Cultivo de Maíz Amarillo (zea mays). San Ignacio, Toacazo, Latacunga - Lárraga Cortéz, Inés Anabel (2018)
The purpose of this investigation project is to evaluate the effect of two composts in combination with a fortifier (wayra) in the cultivation of yellow corn (Zea mays) under water stress conditions and outside the sowing calendar. The researching was carried out in the San Ignacio Community, Toacazo Parish, Latacunga Canton, Cotopaxi Province, at an altitude of 2900 to 3900 meters above sea level. To carry out the research, the following specific objectives were set: Determine the effect of each treatment on the development of the crop (percentage of germination, height, number of leaves), comparing the behavior of the treatments against the attack of pests and diseases and determining the phenological behavior of the crop. The trial was carried out with a designing of Complete Chance Blocks (DBCA), with four repetitions and four treatments. An analysis of variance was performed to verify differences between the selected variables and the Tukey significance test at 5% in the treatments where significance was found. The obtained results for the different variables were: in the percentage of germination it was found that the treatment with the highest percentage was the application of the Wayra silicon-based fortifier, resulting in 86% germination, marking a significant difference compared to the other treatments. For the variables height of plant and number of leaves the application of guinea pig compost + fortifier based on silicon wayra, influenced positively inside these variables, having high values in terms of height an average of 27.50 and the other treatments. Likewise with regard to the incidence of frost was obtained that the treatments: guinea pig compost + fortifier based on silicon wayra and cow compost + fortifier based on silicon wayra, had less percentage of incidence, making the plants more resistant. Although the use of the wayra fortifier mixed with guinea pig compost showed good results by respect to the variables analyzed. It was concluded that when leaving the ideal sowing season it will find disadvantages for the crop. Since the climatic conditions (temperature and precipitation) are different and there are not favorable the normal development of the crop because corn is seasonal and does not support the change of climatic conditions, slowing down the life cycle and making it more sensitive to the attack of pests and frosts.